Perpanjangan Masa Jabatan Presiden Menurut Konstitusi Indonesia - Helfianti, Sutri; Syukriah, Syukriah; Iskandar, Iskandar (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
The 1945 Constitution of the Republic of Indonesia, as the constitution of Indonesia, contains basic rules that are arranged to be used as guidelines or guidelines for the government in carrying out its functions and duties. The Constitution has a role as a barrier to government power in such a way as not to use power arbitrarily. Based on the background of the problems above, the issues that will be discussed are: How is the extension of the President's term of office according to the laws in force in Indonesia? What is the limitation of the term of office of the President in accordance with the constitution of the Republic of Indonesia? This study uses a normative juridical method that emphasizes library research. This means that this research is carried out by paying attention to the applicable laws and regulations. The type of research is qualitative and the approach used is the Statute Approach. This approach is carried out by examining all relevant laws and regulations. Then it is also carried out with a conceptual approach and expert opinion. Limiting the term of office of the President must be carried out according to the constitution, not according to the wishes of the authorities and not also based on political agreements.Keywords: Constitution; Position of President; Indonesia AbstrakUndang-Undang Dasar Negara Republik Indonesia Tahun 1945, sebagai konstitusi Indonesia memuat aturan-aturan dasar yang disusun agar dijadikan pedoman atau pegangan bagi pemerintah dalam menjalankan fungsi dan tugasnya. Undang-Undang Dasar memiliki peranan sebagai pembatas kekuasaan pemerintah sedemikian rupa agar tidak menggunakan kekuasaan dengan sewenang-wenang. Berdasarkan latar belakang permasalahan di atas, maka permasalahan yang akan dibahas adalah: Bagaimanakah perpanjangan masa jabatan Presiden menurut aturan hukum yang berlaku di Indonesia. Bagaimanakah pembatasan masa jabatan Presiden sesuai dengan konstitusi Negara Republik Indonesia. Penelitian ini menggunakan Metode Yuridis Normatif yang menekankan pada penelitian kepustakaan Artinya penelitian ini dilakukan dengan cara memperhatikan aturan perundang-undangan yang berlaku. Adapun jenisnya penelitian adalah kualitatif dan pendekatan yang dilakukan adalah pendekatan Perundang-Undangan (Statute Approach) Pendekatan ini dilakukan dengan menelaah semua peraturan perundang-undangan yang berkaitan. Kemudian juga dilakukan dengan pendekatan konsep dan pendapat para ahli. Pembatasan masa jabatan Presiden harus dilakukan sesuai konstitusi, bukan sesuai keinginan penguasa dan bukan juga atas kesepakatan politik. Kata Kunci: Konstitusi; Jabatan Presiden; Indonesia